Bond-behavior study of newly developed bamboo-composite reinforcement in concrete. (30th September 2016) - Javadian, Alireza; Wielopolski, Mateusz; Smith, Ian F.C.; Hebel, Dirk E.
Highlights: Application of newly developed bamboo-composite material in concrete. Bamboo composite material can serve as reinforcement in concrete. Bamboo-composite reinforcement can develop adequate bonding with concrete matrix. Epoxy-based coating with sand particles could provide extra protection. The new bamboo-composite reinforcement could replace steel reinforcement. Abstract: Bamboo is a rapid growing, affordable and available natural resource in many developing countries. It is potentially superior to timber and to construction steel in terms of its weight to strength ratio. A new technology has been developed in this research to preserve the mechanical properties of bamboo and to enhance physical characteristics through composite action for application in structural concrete. The goal of present work is to investigate the bonding properties of a newly developed bamboo-composite reinforcement in concrete through pull-out testing. Various coatings are applied to determine bonding behavior between concrete and newly developed bamboo-composite reinforcement. The results of this study demonstrate that bamboo-composite reinforcement without coating develops adequate bonding with the concrete matrix. However an epoxy based coating with sand particles could provide extra protection without loss of bond strength.